More planet and less profit? The ethical dilemma of an oil producing nation - John A. Hunnes (Cogent Business & Management, 2019)
Every oil producing nation is confronted with a complex and fundamental ethical dilemma. On the one hand, there are moral arguments for the nation to use the petroleum resource for the benefit of society and make it available for countries who do not have this natural resource endowment. On the other hand, there are moral arguments for not extracting and using fossil fuels because of CO2 emissions. In short, this creates tension between the need for government revenues to finance welfare benefits and the objective of preserving the environment. A complicating factor is that a nation's domestic oil and gas activities are in its nature global because the activities have a direct impact on the global climate. In this paper, I address a question that to my knowledge is rarely discussed in the business ethics literature: how does an oil producing nation try to resolve this fundamental ethical dilemma? Using Norway as a case, I argue that the nation is well aware of this ethical dilemma, but that there are few signals from the government that it wants to reduce the petroleum activities. Instead, Norway tries to seek redemption by (1) using the financial power of the Oil Fund to promote sustainability issues abroad and (2) building an international brand as an 'Environmentally Conscious Energy Nation.'
Keywords: 650; ethical dilemma; sustainability; petroleum; oil; sovereign wealth fund